From Zero to Hero: Global Learning Packets with Parental Involvement at Homes on the Non-Numerates’ Numeracy Level - MARK JOHN A. BELLEZA (International Journal of Scientific Research and Innovative Studies, 2022)
This study sought to determine the effectiveness of Global Learning Packets with parental involvement at homes on thirty-one non-numerates learners' numeracy level specifically on multiplication and division during the pandemic times. The intervention was made possible through the collaboration between the PhD students at the University of West Georgia, USA as the instructional designers and the PhD student of West Visayas State University in the Philippines as the instructional implementer which lasted for six weeks. The main sources of data were the result of a 20-item Regional Unified Numeracy Test (RUNT) administered before and after the intervention, incidental interviews to parents during retrieval and distribution of self-learning modules, and parents’ remarks while learning at home and teachers’ observations during home visitations. After careful analysis, results revealed that the Global Learning Packets with parental involvement at home was effective in improving the numeracy level of the learners with a big shift from "low" to "high". Further analysis revealed that there is a significant difference in the numeracy level of the learners before and after exposure to Global Learning Packets affirming its effectiveness, thus the phrase "zero to hero". It is therefore recommended that (1) non-numerate learners’ should be taught frequently using the global learning packets to improve the learners’ numeracy level, (2) constant collaboration and communication between the teachers and parents as learning facilitators must be strengthened so that learners develop their greatest potentials, and (3) continuous innovations in the curriculum, specifically in instruction is highly encouraged to improve the educational system which will hopefully lift our global ranking.